Electroacupuncture alleviates damage to myopic RGCs probably through lncRNA-XR_002789763.1-mediated mitophagy - Xuejun Wang; Qinghong Lin; Li Tian; Xiaoying Li; Teruko Fukuyama; Weijung Ten; Xiehe Kong; Yanting Yang; Xiaopeng Ma; Xingtao Zhou (Chinese Medicine)
Abstract Background Mitophagy is closely related to the regulation of retinal ganglion cell (RGC) structure and function. Our previous study suggested that long noncoding RNAs (lncRNAs) can cause damage to myopic RGCs. However, whether electroacupuncture (EA) treatment can delay myopia progression through lncRNA-mediated mitophagy in RGCs is currently unknown. This study aimed to investigate the effect of EA on lncRNA-mediated mitophagy in myopic RGCs. Methods Our study investigated the modulatory effect of EA on mitophagy in RGCs of guinea pigs with form-deprived myopia (FDM). RNA sequencing was performed to further analyze the expression profiles of lncRNAs and mRNAs in RGCs of guinea pigs with FDM after EA treatment, and the related competing endogenous RNA (ceRNA) network was constructed. Importantly, PINK1, a mitophagy-related gene, was included in the core ceRNA network to explore the relationship between lncRNAs and mitophagy in myopic RGCs regulated by EA. We also collected eyeballs from myopic and highly myopic adults to further verify the mechanistic results. Results This study demonstrated that EA treatment delayed the reduction in refraction and increase in axial length and alleviated RGC damage in guinea pigs with FDM. We further found that EA could induce mitophagy in guinea pig RGCs with FDM by promoting the mitophagy-related PINK1/Parkin signaling pathway. Moreover, mitophagy is inhibited in the retina of highly myopic adults. RNA sequencing revealed that 599 lncRNAs and 455 mRNAs were differentially expressed in guinea pig RGCs with FDM after EA treatment. A core ceRNA network was constructed by incorporating PINK1 and verified by related molecular experiments, and we found that EA treatment may induce mitophagy and attenuated RGC injury in guinea pigs with FDM by sponging miR-342-5p through lncRNA-XR_002789763.1 to activate the PINK1/Parkin signaling pathway and promote Mfn2 ubiquitination. Conclusion EA treatment might regulate lncRNA-XR_002789763.1/miR-342-5p axis and activate the mitophagy-related PINK1/Parkin signaling pathway, and promote Mfn2 ubiquitination, thereby alleviating RGC damage and delaying myopia progression.